Post-Operative Management for Craniotomy Decompression in Cerebral Edema Patients Due to Cerebral Infarction in The Right Carotic System which Occurred Cerebral Vasospasm - Halimi, Radian Ahmad; Zulfariansyah, Ardi (Journal of Society Medicine, 2024)
Introduction: Cerebral infarction accompanied by brain edema is a life-threatening condition and requires decompression craniectomy to overcome increased intracranial pressure (ICP). Comprehensive post-operative management using non-invasive transcranial doppler (TCD) monitoring and Near Infrared Spectroscopy (NIRS) is a modality for conducting management in the intensive room (ICU). Case Report: We reported the case of a 56-year-old man diagnosed with cerebral edema due to stroke infarction of the right carotid system accompanied by comorbidities of coronary heart disease with a heart ejection fraction of 31.6% performed craniectomy decompression. The patient was treated for 12 days in intensive care and then transferred to a semi-intensive room Conclusion: This case highlights the importance of using TCD and NIRS in the intensive care unit as guiding therapies in maintaining patient blood pressure, administering blood components, and early detection of complications such as cerebral vasospasm.